Plant density and nitrogen fertilization optimization on sorghum grain yield in Mali - Dembele, Joseph Sékou B; Gano, Boubacar; Kouressy, Mamoutou (Wiley Periodicals LLC, 2021)
Sorghum [Sorghum bicolor (L.) Moench], a staple food crop in Mali, has low yields for several reasons including that many farmers do not have the financial resources to purchase state-of-the-art genetics and fertilizers and information is not available on how to optimize yields for heirloom variety. To improve their economic and environmental sustainability, Mali farmers need to understand how to invest their limited resources. In many situations this involves the use of open-pollinated varieties that have a range of tillering capabilities. This study determined the best population density and nitrogen (N) fertilization combinations for eight locally available sorghum varieties. The research was conducted in 2018 and 2019 and the experimental design was split-split-plot randomized block, the treatments were two plant densities (26,600 and 53,300 plants ha–1), three N levels (0 kg ha–1, 89 kg ha–1, and 178 kg ha–1), and eight varieties that had a range of tillering characteristics. Each treatment was replicated three times and six of the varieties were open pollinated. Results showed that each variety had a different yield response to plant density and N rate. For example, the tall guinea (hybrids FADDA and PABLO) and the short durra-caudatum A12-79 cultivar produced higher yields when planted at 53,300 plants ha–1 and fertilized with 178 kg N ha–1 N2D2 treatment. For the short guinea-caudatum improved varieties C2_007-03 and C2_075-15 and caudatum GRINKAN and SOUMBA varieties the optimum seeding rate was 53,300 plants ha–1 that were fertilized with 89 kg N ha–1 (N1D2). For the tall local guinea TIEBILE variety the highest yields were observed when it was seeded at a rate of 26,600 plants ha–1 and fertilized with 89 kg N ha–1. Grain yield increase was associated with yield components and growth traits for eight varieties studied. Panicle numbers per square meter and chlorophyll index were associated with grain yield in guinea hybrid. Grain number per panicle and 1,000 grain weight were involved in increasing grain yield in caudatum varieties. Nitrogen rate and planting density combination in terms of grain yield varied with different sorghum [Sorghum bicolor (L.) Moench] varieties studied. Knowledge of optimum combinations will help producers decide which option to promote to booster sorghum production in Mali.
Agronomy Journal Vol113, (6) p. 4705-4720
Keywords: Léonce Lamine Dembele; Mohamed Doumbia; Komla Kyky Ganyo; SékouBa Sanogo; Adama Togola; Karim Traore; Michel Vaksman; Niaba Teme; Diaga Diouf; Alain Audebert; AGRISAN; Université Cheikh Anta Diop; Sénégal; nitrogen fertilization; Plant density; Sorghum